How many testers are needed to assure the usability of medical devices? - Borsci, Simone; Macredie, Robert D.; Martin, Jennifer L.; Young, Terry (Taylor & Francis, 2014)
Before releasing a product, manufacturers have to follow a regulatory framework and meet standards, producing reliable evidence that the device presents low levels of risk in use. There is, though, a gap between the needs of the manufacturers to conduct usability testing while managing their costs, and the requirements of authorities for representative evaluation data. A key issue here is the number of users that should complete this evaluation to provide confidence in a product's safety. This paper reviews the US FDA's indication that a sample composed of 15 participants per major group (or a minimum of 25 users) should be enough to identify 90-97% of the usability problems and argues that a more nuanced approach to determining sample size (which would also fit well with the FDA's own concerns) would be beneficial. The paper will show that there is no a priori cohort size that can guarantee a reliable assessment, a point stressed by the FDA in the appendices to its guidance, but that manufacturers can terminate the assessment when appropriate by using a specific approach - illustrated in this paper through a case study - called the 'Grounded Procedure'.